Calcium intake and serum concentration in relation to risk of cardiovascular death in NHANES III. - Mieke Van Hemelrijck (Public Library of Science (PLoS), 2013)
Background Evidence for an association between calcium intake and risk of cardiovascular death remains controversial. By assessing dietary intake, use of supplements, and serum levels of calcium, we aimed to disentangle this link in the third National Health and Nutrition Examination Survey (NHANES III). Methods Mortality linkage of NHANES III to death certificate data for those aged 17 years or older (n = 20,024) was used to estimate risk of overall cardiovascular death as well as death from ischemic heart disease (IHD), acute myocardial infarction (AMI), heart failure (HF), and cerebrovascular disease (CD) with multivariate Cox proportional hazards regression analysis. Results About 10.0% of the population died of cardiovascular disease and the majority (5.4%) died of IHD. There was increased risk of overall CVD death for those in the bottom 5% of serum calcium compared to those in the mid 90% (HR: 1.51 (95% CI: 1.03-2.22)). For women there was a statistically significant increased risk of IHD death for those with serum calcium levels in the top 5% compared to those in the mid 90% (HR: 1.72 (95%CI: 1.13-2.61)), whereas in men, low serum calcium was related to increased IHD mortality (HR: 2.32 (95% CI 1.14-3.01), Pinteraction: 0.306). No clear association with CVD death was observed for dietary or supplemental calcium intake. Conclusions Calcium as assessed by serum concentrations is involved in cardiovascular health, though differential effects by sex may exist. No clear evidence was found for an association between dietary or supplementary intake of calcium and cardiovascular death.